A partial encryption scheme using absolute-value chaotic map for secure electronic health records - S. Fong-In (2018)
This paper presents a partial encryption scheme using absolute-value chaotic map for secure electronic health records (EHR). The HER system has been an emerging technology that allows medical personals to create, manage, and control medical data electronically through specific database or even web browsers. The proposed encryption scheme realizes XOR operations between separated planes of binary gray-scale image and a binaty imgae generated by an absolute-value chaotic map. The proposed is relatively simple containning a single absolute-value function with two constants and offers complex and robust dynamical behaviors in terms of random output values. Experiments have been performed in MATLAB using a magnetic resosnace image which is divided into 64 sub-blocks and 13th itterations were proceeded for encryption. Encryption qualitative performances are evaluated through pixel density histograms, 2-dimensional power spectral density, and vertical, horizontal, and diagonal correlation plots. For the encryption quantitative measures, correlation coefficients, entropy, NPCR and UACI are realized. Demonstrations of wrong-key decrypted image are also included. The proposed encryption scheme offers a potential alternative to a secure medical data records and web browsing through clound computing systems. © 2014 IEEE.